Pioneer life in western Pennsylvania - Wright, J. E. (John Ernest), 1894- (Pitt paperback ;, 1996)
A fascinating look at life during pioneer times in western Pennsylvania. Describes the hardship, danger and drudgery of day-to-day life on the frontier. Topics include cabin raising, crop harvests, tanning, weaving, disease, religion, and superstition. Also follows the progression from pioneer life to industrial society.